Infrastruktur Berkelanjutan dan Smart City: Strategi Birokrasi dalam Mencapai Indonesia Emas 2045 - Shoum Abdurrohman, Sholahuddin; Irwani, Irwani; Anzarach Pratama, Muhammad (Jurnal Ilmu Administrasi Negara AsIAN (Asosiasi Ilmuwan Administrasi Negara), 2024)
To Indonesia Emas 2045 vision, the study will investigate bureaucratic methods that combine the concept of smart cities and sustainable infrastructure. The research uses literature analysis and policy documents on smart cities and sustainable infrastructure. Research shows that integrating smart cities and infrastructure can improve resource efficiency, reduce environmental impact, and improve the quality of life of people. This article discusses the role of bureaucracy in creating policies that support cooperation between the public and private sectors as well as improving public services through the use of digital technology. Besides, the problems faced include technological constraints, funding shortages, and discomfort for change. This research found that the sustainable implementation of smart cities relies heavily on governments to make comprehensive and inclusive policies. Using the right bureaucratic approach, smart city integration and sustainable infrastructure can be key pillars in achieving Indonesia’s Golden 2045, where economic growth, environmental sustainability, and social well-being can be achieved simultaneously.